Arterial tortuosity syndrome: A rare entity - Marwah Ashutosh; Shah Sejal; Suresh P; Maheshwari Sunita (Wolters Kluwer Medknow Publications, 2008)
We present a 5 month old baby who was referred for an incidental detection of a murmur and was found to have tortuous pulmonary arteries with multiple peripheral pulmonary stenoses and bilateral inguinal hernia pointing towards the diagnosis of arterial tortuosity syndrome.